2011
DOI: 10.1007/s10165-011-0461-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exon 2 skipping caused by c.910G>A variant and alternative splicing of MEFV genes in two independent cases of familial Mediterranean fever

Abstract: Most reported cases of familial Mediterranean fever (FMF) involve missense mutations of MEFV concentrated within exon 10. We experienced two independent pedigrees of a unique variant in the MEFV gene that might cause excessive exon 2 skipping due to enhanced alternative splicing. In this study, we tried to elucidate the molecular mechanism of the MEFV variant as a cause of the FMF phenotype. Peripheral blood was obtained from volunteers and two patients with homozygous c.910G>A variant of the MEFV gene. MEFV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These variations appeared to have a role in the pathogenesis of TRAPS disease ( Rittore et al , 2014 ). Furthermore, in another study, Tone et al (2011) suggested that c.910G > A variant (rs75977701) leads to the skipping of MEFV exon 2. This rare variant, which has a Minor Allele Frequency (MAF) of T = 0.0074/37 in the Thousands Genomes Project, was absent in our FMF cohort.…”
Section: Discussionmentioning
confidence: 98%
“…These variations appeared to have a role in the pathogenesis of TRAPS disease ( Rittore et al , 2014 ). Furthermore, in another study, Tone et al (2011) suggested that c.910G > A variant (rs75977701) leads to the skipping of MEFV exon 2. This rare variant, which has a Minor Allele Frequency (MAF) of T = 0.0074/37 in the Thousands Genomes Project, was absent in our FMF cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, defects affecting only a fraction of the transcripts produced and mostly evidenced on sequencing electrophoregrams are more difficult to interpret in terms of disease causality. This is even more problematic when a VUS seems to strengthen an alternative splicing pattern, as inappropriate levels of isoforms can be damaging to the cells [Brezin et al, 2011; Tone et al, 2012]. Quantitative evaluation of partial splicing defects therefore cannot be based on inspection of sequencing electrophoregrams.…”
Section: Discussionmentioning
confidence: 99%
“…The MEFV gene underwent direct sequencing, as described previously. 6 Serum concentrations of cytokines were determined using enzyme-linked immunosorbent assay kits: neopterin (IBL, Hamburg, Germany); IL-6; soluble tumor necrosis factor (TNF) receptor type 1 (sTNF-RI) and type 2 (sTNF-RII; R&D Systems, Minneapolis, MN, USA); and IL-18 (MBL Co., Ltd, Nagoya, Japan). 7 All samples were collected during the afebrile phase in patients with FMF and their family members.…”
Section: Mutation Analysis and Cytokine Determinationmentioning
confidence: 99%